2012
DOI: 10.1186/1471-2164-13-335
|View full text |Cite
|
Sign up to set email alerts
|

A microarray analysis of gnotobiotic mice indicating that microbial exposure during the neonatal period plays an essential role in immune system development

Abstract: BackgroundEpidemiological studies have suggested that the encounter with commensal microorganisms during the neonatal period is essential for normal development of the host immune system. Basic research involving gnotobiotic mice has demonstrated that colonization at the age of 5 weeks is too late to reconstitute normal immune function. In this study, we examined the transcriptome profiles of the large intestine (LI), small intestine (SI), liver (LIV), and spleen (SPL) of 3 bacterial colonization models—specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 47 publications
1
40
1
Order By: Relevance
“…Accordingly, mucosal T cell homeostasis is regulated by the epithelial cell-derived cytokine thymic stromal lymphopoietin (TSLP) by dendritic cell activation and signaling, 26 and this cytokine was also significantly less expressed in the GF mice compared with the SPF mice; however a strong but nonsignificant trend (p = 0.09) existed also for the ex-GF groups. In resemblance to the study by Yamamoto et al, 25 the TLR gene expression was only high subsequent to microbial exposure during the neonatal period. Supportive of this, a low expression of TLRs was similarly seen also after early life antibiotic treatment.…”
Section: Microbial Variation and Host Phenotypesupporting
confidence: 69%
See 1 more Smart Citation
“…Accordingly, mucosal T cell homeostasis is regulated by the epithelial cell-derived cytokine thymic stromal lymphopoietin (TSLP) by dendritic cell activation and signaling, 26 and this cytokine was also significantly less expressed in the GF mice compared with the SPF mice; however a strong but nonsignificant trend (p = 0.09) existed also for the ex-GF groups. In resemblance to the study by Yamamoto et al, 25 the TLR gene expression was only high subsequent to microbial exposure during the neonatal period. Supportive of this, a low expression of TLRs was similarly seen also after early life antibiotic treatment.…”
Section: Microbial Variation and Host Phenotypesupporting
confidence: 69%
“…25 Furthermore, the list of overrepresented signal pathways was different between late colonized ex-GF breast milk and antibiotic therapy. A deviant gut microbiota with less bifidobacteria and more clostridia has for example been reported in both children born by cesarean section (CS) and those with allergies.…”
Section: Window Of Opportunitymentioning
confidence: 99%
“…S7). These data may reflect changes in a TIR-microbiotaenteric virus axis through postnatal development (27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 95%
“…It is important to realize that although GF mice do not harbor live bacteria or archaea, they are not naive to microbial-associated molecular patterns, as they encounter them in their sterilized (by autoclave or irradiation) food, water, and bedding. Microarray-based comparisons of host tissues from GF mice and their conventional counterparts have been a successful approach to understand the broad impact of the microbiome on physiology (Cash et al 2006;Larsson et al 2011;Yamamoto et al 2012). Microarrays of GF and conventionalized mice even have shown that the gut microbiota modulate host gene expression post-transcriptionally by altering expression of host microRNAs within the small and large intestine (Dalmasso et al 2011).…”
Section: Engineered Microbiomes In Micementioning
confidence: 99%